INFLUENCE OF THE EXPIRATORY PRESSURE LEVELS ON THE ALVEOLAR RECRUITMENT OF THE HEALTHY SUBJECTS. - CRAVINHO, Clement; IANC, Dorina (Romanian Journal of Physical Therapy / Revista Romana de Kinetoterapie, 2021)
Few studies have analyzed the effect of different well-defined PEP levels on lung function since the majority of clinical trials use PEP mask and a pressure «fork». The objective of this study is to find out if there is a common level of PEP to be applied which allows optimization of alveolar recruitment, objectivity by tomography by electric impedance, for all subjects. The study was carried out on 14 healthy participants, 7 men and 7 women, aged 22 to 30. Participants had a exhale against four resistors of different values, determined by the tension of the spring, 5, 10, 15 and 20cmH20. The measurement of alveolar recruitment during the experiment was carried out by an electrical impedance tomograph. Each participant reacted differently to the PEP levels, but by comparing the responses of the pulmonary function, it is noted that the individual characteristics can influence the alveolar recruitment, whatever the level of resistance applied. It would be interesting to investigate, on a larger sample and with several groups of participants with low inter-individual variability, whether there is a correlation between individual characteristics and the potential for alveolar recruitment. This would optimize care by adapting it to each subject.